Pengaruh Kualitas Ruang Terbuka Publik Terhadap Ekspektasi Pengguna di Taman Alun-alun Kapuas, Kota Pontianak - Awtayuda, Adly (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
The open space area is a place of social interaction, such as Taman Alun-alun Kapuas in Pontianak. The objective of this study is to asses the effect of the quality of public open space in Pontianak against the usesrs’ expectations. The study using quantitative method by observation, interview, and distributing the questionnaire. The respondents are the users in the location that determined based on probability sampling techniques. The analysis of qualitative descriptive is used to assess the quality based on the facts in the location. The users’ expectation is analyzed by multiple regression analysis with 5 (five) variables: comfort variable (climatology and facilities); relaxation variable (separator ways, ornament, safety); involvement of passive variable (observation, landscape and natural elements); active involvement variable (ease of doing activities, space of communication, event, and playground); as well as variable discovery (characteristic of the area). The result of this research shows that: the name of Taman Alun-alun Kapuas doesn’t have any relevance with the Alun-alun concept in Java. The high temperature of Pontianak causing many users visit Taman Alun-alun Kapuas in the evening which tends to be a passive activities; there are six indicators which has met the expectations of users: the separator ways, landscape of garden, the observation, freedom of movement, space of communication, and characteristic of areas.; the street vendors in Alun-alun Kapuas has the positive and negative impacts for the users.